Cytotoxicity and inflammatory effects in human bronchial epithelial cells induced by polycyclic aromatic hydrocarbons mixture. Issue 11 (29th March 2021) - Wang, Hong; Liu, Jinren; Kong, Qingbo; Li, Liang; Gao, Junhong; Fang, Le; Liu, Zhiyong; Fan, Xiaolin; Li, Cunzhi; Lu, Qing; Qian, Airong
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are the most common contaminants in the air pollutants. Inhalation exposure to PAHs could increase the risk of respiratory disease, cardiovascular disease and even cancer. However, the biotoxicity of multi‐component PAHs from atmospheric pollutants has been poorly studies. The main topic of this study was to investigate the PAHs mixture, which derived from atmospheric pollutants, induced toxic effects and inflammatory effects on human bronchial epithelial cells in vitro. The results showed that PAHs mixture could decrease the cell viability, increase the apoptosis rate, and induce cell cycle arrest at S‐phase. Furthermore, the expression of inflammatory factors IL‐1β and IL‐6 were increased and NF‐κB signaling pathway was activated in PAHs mixture‐treated cells. The findings of this study indicate that PAHs mixture‐induced cytotoxicity and inflammation may be related to intracellular ROS generation and to the activated NF‐κB signaling pathway. Abstract : We investigated that the PAHs mixture induced toxic effects and inflammatory effects on human bronchial epithelial cells in vitro. The results showed that PAHs mixture could decrease the cell viability and increase the apoptosis rate. In addition, the expression of inflammatory factors IL‐1β and IL‐6 was increased in PAHs mixture‐treated cells. These may be related to intracellular ROS generation and NF‐κB signaling pathway activation.